Angiogenesis in Schistosoma haematobium‐associated urinary bladder cancer. Issue 12 (28th September 2017) - Dematei, Anderson; Fernandes, Rúben; Soares, Raquel; Alves, Helena; Richter, Joachim; Botelho, Monica C.
Abstract : Schistosoma haematobium, a parasitic flatworm that infects more than 100 million people, mostly in the developing world, is the causative agent of urogenital schistosomiasis, and is associated with a high incidence of squamous cell carcinoma (SCC) of the bladder. During infection, eggs are deposited in the bladder causing an intense inflammatory reaction. Angiogenesis is defined as the formation of new blood vessels from preexisting ones and is recognized as a key event in cell proliferation and carcinogenesis and spread of malignant lesions. A growing amount of evidence points to angiogenesis playing a key role in schistosomiasis‐associated bladder cancer. Thus, identifying biomarkers of this process plays an important role in the study of cancer. Here, we review recent findings on the role of angiogenesis in bladder cancer and the growth factors that induce and assist in their development, particularly SCC of the bladder associated to urogenital schistosomiasis.